2019
DOI: 10.1080/00140139.2019.1614212
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a tailored workplace intervention designed to promote sustainable working in a rapidly changing world

Abstract: Increasing numbers of people are employed in sedentary occupations, spending large amounts of time sitting at work which is detrimental to health and wellbeing. Evidence-based guidance is required to intervene to reduce sedentary behaviour, encourage physical activity and promote sustainable working. This article presents a process evaluation of a successful workplace intervention Walking Works Wonders, shown to be effective in improving health, job satisfaction and motivation (Haslam et al. 2018). In this qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With a weak quality of evidence, a positive effect for valuable work outcomes was found only in four out of nine interventions covering no more than two SE core components in their intervention content [44,45,48,51]. Only three out of five studies addressing the health component in their intervention content found positive health outcome effects [38,40,43].…”
Section: Effectiveness Of Se Interventions In Fostering Se Core Compo...mentioning
confidence: 98%
See 1 more Smart Citation
“…With a weak quality of evidence, a positive effect for valuable work outcomes was found only in four out of nine interventions covering no more than two SE core components in their intervention content [44,45,48,51]. Only three out of five studies addressing the health component in their intervention content found positive health outcome effects [38,40,43].…”
Section: Effectiveness Of Se Interventions In Fostering Se Core Compo...mentioning
confidence: 98%
“…Intervention effects, those on outcomes in line with intervention content or not, may be explained with complex mediating and moderating processes [77]. In our review of studies, only five out of fourteen studies included an intervention process evaluation [36,37,41,51,78]. When the program failed, the authors reported reasons such as a short duration, a lack of training frequency, an inadequate level of skills, or low adherence to the program [34,35,39,49,78].…”
Section: Practical and Societal Implicationsmentioning
confidence: 99%